The therapeutic potential of mesenchymal stem cells in intestinal diseases: from mechanisms to clinical translation - Jia-Zhi Yang; Li-Yan He; Xian-Zhou Lu (Stem Cell Research & Therapy)
Abstract Current therapeutic interventions for intestinal pathologies, including anti-inflammatory agents, immunosuppressants, and surgical procedures, frequently incur substantial adverse effects, elevated recurrence rates, and suboptimal tissue regeneration. Cellular therapy has emerged as a paradigm-shifting strategy, capitalizing on regenerative potential and immunomodulatory properties. Mesenchymal stem cells (MSCs), distinguished by their potent immunoregulatory capacity and multipotent differentiation plasticity, have recently demonstrated remarkable therapeutic promise in inflammatory bowel disease (IBD), ischemia–reperfusion injury, oncological interventions, and radio-chemotherapy-induced complications. This systematic review critically evaluates MSC biological characteristics, clinical translation progress, and cutting-edge advancements in tissue engineering applications. Mechanistic insights into MSC-mediated intestinal repair are elucidated, with particular emphasis on emerging evidence suggesting MSC-derived exosomes may modulate ZBP1-associated H3K27 acetylation to attenuate intestinal epithelial apoptosis—a novel epigenetic regulatory axis for gastrointestinal restitution. Future translational trajectories and clinical implementation challenges are comprehensively discussed.